The Contributions of Nigerian Writers in Translating Some Literary Works into Arabic Language: Literature - Atotileto, Abdussalam Aminu; Abdussalam, Uthman (Al-Ḍād Journal, 2024)
Abstract This study examines the noteworthy contributions of Nigerian writers in the translation of literary works into the Arabic language. As part of the growing global exchange of literary ideas, Nigerian authors have played a pivotal role in bridging cultural and linguistic gaps by translating their works, as well as the works of others, into Arabic. The research delves into the motivations, challenges, and impact of these literary translations, examining the impact on the reception of Nigerian literature in Arabic-speaking communities. Additionally, the study sheds light on the challenges faced by these writers in the translation process and the strategies employed to overcome them. exploring the socio-cultural context, it is also aims to shed light on the nuanced process of bringing Nigerian literature to an Arabic-speaking audience. Through this investigation, the research contributes to a deeper understanding of cross-cultural literary exchange and highlights the role of Nigerian writers in fostering linguistic diversity and cultural dialogue. Furthermore, the researcher observes that writers in Nigeria have played an active role in the translation movement, contributing to the development of the Arabic language. Notable figures include Professor Isaac Ogunbiyi, who translated a collection of Yoruba folktales from Yoruba to Arabic, titled "Folk Stories about the Turtle among the Yoruba," in 1974. The late Dr. Olalere Adigun (d. 1991) also translated an English novel into Arabic titled "The African Night Entertainment" in 1994. Additionally, Professor Masoud Raji translated an English novel into Arabic titled "The Burning Grass" in 1997. Moreso, Professor Ahmed Sheikh Abdul Salam translated a Yoruba novel into Arabic titled “Ireke Onibudo” in 1994, and Professor Mashood Mahmoud Jimba translated another Yoruba novel into Arabic titled "The Bold Hunter in the Forest of Spirits" (Ogboju Ode Ninu Igbo Olodumare) in 2002, others. This research adopts a descriptive exploratory approach and an analytical method, extracting samples from books translated into Arabic by Nigerian writers. Keywords: Literary, Translation, Arabic, Nigerian, Cultural Exchange